Estimating Exchange Rate Dynamics with Diffusion Processes: An Application to Greek EMU Data - Bernd Wilfling; Mark Trede (Hamburg Institute of International Economics (HWWA), 2004)
Recently various exchange rate models capturing the dynamics during the transition from an exchange rate arrangement of floating rates into a currency union have been derived. Technically, these stochastic equilibrium models are diffusion processes which have to be estimated by discretely sampled observations. Using daily exchange rate data prior to the Greek EMU-entrance in January 2001 this paper develops a rigorous estimation procedure. The estimates provide statistical evidence of increased central bank intervention activities in the run-up to the Greek EMU entrance. Thus the modelling and estimation framework establishes an approach for detecting intervention phases in the absence of concrete intervention data.
Keywords: F33; F31; C13; C22; 330; Diffusion processes; estimation; exchange rates; EMU; central bank interventions; Wechselkurs; Wechselkurstheorie; Stochastischer Prozess; Dynamisches Modell; Europäische Wirtschafts- und Währungsunion; Schätzung; Theorie; Griechenland